KEJAHATAN PENISTAAN AGAMA DAN KONSEKUENSI HUKUMNYA - Muhammad Hatta; Husni, Zulfan (Al-Adl : Jurnal Hukum, 2021)
This study aims to analyze the regulation and enforcement of criminal law against the crime of blasphemy (religious defamation). The method used in this research is the normative method which is carried out by examining the laws and regulations that are applied to particular legal problems. The results of this study state that Indonesia recognizes religions and divinity so that the first principles of Pancasila and the Preamble to the 1945 Constitution explicitly state the recognition of divinity by various religions and beliefs. Therefore, every person is obliged to adhere to a certain religion and belief in its truth. However, every religious adherent must maintain harmony between communities both in carrying out their worship and implementing laws that are believed to be true. One of the actions that often trigger clashes between communities is the act of blasphemy. Along with the development of Information and communication technology, acts of blasphemy are widely spread in various virtual media, both on social media and news media. To maintain harmony, the government strictly enforces the law against crimes of religious blasphemy on various laws and regulations such as the Penal Code and Act 19/2016 on Amendments to Act 11/2008. Therefore, all offenders of religious blasphemy in Indonesia will face legal consequences according to their actions.